UTILIZING A GEOSPATIAL INFORMATION SYSTEM (GIS) TO ANALYZE CURRENT COMMUNITY HEALTH CENTER FACILITIES ACCESSIBILITY IN KABUPATEN BANDUNG, INDONESIA - Alfasya Putra Faizal, Muhammad
As the demand for healthcare grows the need for accurate data is needed for future strategic decisions. To effectively meet the demand, the West Java Ministry of Health planned to conduct a digital transformation that would ease the process such as digitalization. This research aims to analyze the supply and demand of Kabupaten Bandung Community Health Centers (CHCs) as a step towards that transformation. CHCs play a crucial role in improving public health, where most cases are initially reported, services provided by CHCs are detrimental to the surrounding public, not only to providing medical treatment but other governmental health policies to increase the quality of life in the area. Kabupaten Bandung not only being the biggest regency in West Java but also presented a unique challenge for resource allocation due to its topography. With three million people scattered across 31 sub-regencies being presented in a data-accurate location would ease the decision-making process for CHCs or other uses for healthcare facilities. Recent health report shows the distribution of CHCs, where 19 of the 31 sub-districts have 2 Community Health Centers, while some sub-regencies have 1 or 3 CHCs. The demand gap could cause the healthcare services to be less than optimal and assess how well the people who live in the area access this healthcare. Improving healthcare accessibility requires strategic allocation of resources. To overcome the problems of excess capacity and unequal distribution, this research advocates for fairer access to healthcare for all residents of Kabupaten Bandung. Utilizing a Geographic Information System (GIS) and descriptive data analysis to assess the Kabupaten Bandung CHCs' service area coverage and capability. Evaluating the existing distribution of healthcare services using ArcGIS Service Area Analysis and Tableau's supply and demand visualization feature. Based on service area analysis, the CHCs in the Kabupaten Bandung area are effectively accessible, with the service area collectively covering 63% (1,094.1 km2) when clinics are included that effective service range reach-up to 64.4% (1,125 km2). On average, Kabupaten Bandung each CHC serves 59,978 people, more than the Target Nasional standards of 30,000 people and the provincial average of 45,507 people. This is further proven by most of its sub-regencies failing to meet the demands of its population. To effectively plan for future healthcare facilities the map model located each CHC in each subregencies and the effective service area based on the effective travel time (30 Minutes), while the tableau dashboard visualizing the location of each sub-regency’s demand for CHCs based on the Target Nasional. i